Constituintes químicos e avaliação de atividades biológicas de Croton polyandrus Spreng. (Euphorbiaceae) - Fernandes, Heloísa Mara Batista (2012)
The family Euphorbiaceae is the sixth largest family of plants in the world represented by 300 genera and 8000 species. Among the many genres that make up this family, the genus Croton stands as the second largest, with about 1300 species, having a neotropical distribution. This genus has been the most studied, due in large part to the chemical compounds produced by this promising group. To contribute to the chemotaxonomic study of the genus Croton and family Euphorbiaceae, the extract of C. polyandrus was subjected to a phytochemical study to isolate chemical constituents through usual chromatographic methods, and then to identify them by means of spectroscopic methods, such as IR, 1H-NMR and 13C and uni-dimensional, spectometryc such as spectrometry mass, and compared with literature data. The chemical study of the aerial parts and roots of C. polyandrus resulted in the identification of nine substances: oxide β-caryophyllene (Cp-1), β-sitosterol (Cp-2), sitosterol-3-O-β-D-glucopyranoside (Cp-3); pheophytin A (Cp-4); Carvacrol (Cp-5), 5-β-hydroxy-2-oxo-p-ment-6 (1)-ene (Cp-6), 3-methoxy-4-hydroxy-benzaldehyde (Cp-7), 1,2,3,4-tetrahidroxi-p-mentano (Cp-8); Sucrose (Cp-9), being the nine first reported in this species. The chemical composition of essential oil had thirty-three components, among which p-cymene (12.4%) showed a major compound with. The essential oil of C. polyandrus were tested against strains of gram positive and gram negative strains of Candida, and cancer cell lines. The essential oil of C. polyandrus tested showed no antibacterial activity, however, showed considerable antifungal and cytotoxic to all cell lines only at the highest concentration tested, using the values of TGI, the essential oil was inactive against the tumor cell lines.